Efektywność gospodarcza a sprawiedliwość podatkowa proporcjonalnego i progresywnego opodatkowania dochodów osób fizycznych - Podstawka, Marian; Deresz, Agnieszka (Economic Effectiveness and Tax Justice of Proportionate and Progressive Taxation on Individual Income, 2009)
This study focuses on progressive and proportionate income tax imposed on individual taxpayers taking into account its effectiveness and justice. The assessment is based on a theoretical approach
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 244-251